Advances in therapeutic options for portal hypertension. (November 2018) - Vilaseca, Marina; Guixé-Muntet, Sergi; Fernández-Iglesias, Anabel; Gracia-Sancho, Jordi
Portal hypertension represents one of the major clinical consequences of chronic liver disease, having a deep impact on patients' prognosis and survival. Its pathophysiology defines a pathological increase in the intrahepatic vascular resistance as the primary factor in its development, being subsequently aggravated by a paradoxical increase in portal blood inflow. Although extensive preclinical and clinical research in the field has been developed in recent decades, no effective treatment targeting its primary mechanism has been defined. The present review critically summarizes the current knowledge in portal hypertension therapeutics, focusing on those strategies driven by the disease pathophysiology and underlying cellular mechanisms.